Des acteurs transnationaux dans le développement latino-américain - Alschuler, Lawrence (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1986)
Our aim in this article is to identify the major transnational actors and to describe how they have influenced Latin American politics and development from the 1950s to the present. Transnational actors are defined as those collective actors (here non-governmental) whose membership and activities are transnational. Specifically ex-amined are the multinationals, the Catholic Church, international labor confederations, and guerrilla movements. The historical context within which we study these actors has two periods : early import substitution (1954-65) and late import substitution and export substitution (1965 to present). In each period the state pursue s a development strategy with the support of particular class alliances. For each period we describe how the transnational actors contribute to the successes and failures of these strategies. The causal relations are also reciprocal, for the actors evolve and adapt to the changing developmental context. For example, the multinationals shift from raw material extraction to manufacturing while the Church shifts from conservatism to the theology of liberation. The general trends in the activities of transnational actors over the post war period are interpreted with respect to the twin polarities of the development process : opression - liberation, integration - autonomy.